Pengaruh Transformasi Sistem Pencatatan Keuangan Dan Diigital Marketing Dengan Financial Technology Sebagai Variabel Moderasi Terhadap Profitabilitas UKM Kota Makassar - Arsyad, Muh Rifai; Nurwanah, Andi; Nur, Muhammad (Jurnal Ilmiah Akuntansi Peradaban, 2023)
The SME sector plays an important role in national economic growth. The recovery adaptation period brings new opportunities for the SME sector to develop and improve. This research aims to provide a more comprehensive view of how the application of financial recording system transformation, digital marketing and the role of financial technology can increase SME profitability, especially in Makassar City. The data in this study were obtained from SMEs in Makassar City under the auspices of the Makassar City Cooperative and SME Office who were willing to be respondents. This study uses primary and secondary data by conducting direct research in the field by giving a questionnaire / statement sheet to 102 respondents. The data analysis technique was carried out by descriptive statistical analysis and PLS (Partial Least Square). The results showed that the Transformation of the Financial Recording System and Digital Marketing had a positive and significant effect on the Profitability of SMEs in Makassar City.